2021
DOI: 10.5005/jp-journals-10005-1894
|View full text |Cite
|
Sign up to set email alerts
|

Parental Awareness and Knowledge toward their Children\'s Oral Health in the City of Dammam, Saudi Arabia

Abstract: A bstract Introduction Two main factors have a great influence on the youth's oral well-being. These are their dental health and age. These two factors are significantly directed by parents through establishing a system of proper oral hygiene and a preventative routine for those young adults. Aim and objective The following study was run in the Dammam region, Saudi Arabia, to assess guardian awareness of youngster's dental health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
2
16
1
1
Order By: Relevance
“…Parental oral health knowledge has been reported by many authors to be considerably affected by sociodemographic characteristics. [61][62][63] However, in the present study, there were no differences in the total knowledge score across parents with various background characteristics, which may have been attributed to the homogenous sample in the present study because we recruited parents seeking dental treatment for their children at a governmental hospital. Moreover, our findings were consistent with other studies that did not find any relationships between parental sociodemographic characteristics and levels of oral health knowledge.…”
Section: Discussionmentioning
confidence: 57%
“…Parental oral health knowledge has been reported by many authors to be considerably affected by sociodemographic characteristics. [61][62][63] However, in the present study, there were no differences in the total knowledge score across parents with various background characteristics, which may have been attributed to the homogenous sample in the present study because we recruited parents seeking dental treatment for their children at a governmental hospital. Moreover, our findings were consistent with other studies that did not find any relationships between parental sociodemographic characteristics and levels of oral health knowledge.…”
Section: Discussionmentioning
confidence: 57%
“… 8 Many children and parents in developing nations have limited awareness of the causes and prevention of the most frequent oral diseases. 9 Oral health knowledge among Indian children is low when compared with their western counterparts. 10 It has been found that inculcating preventive oral hygiene behaviour among schoolchildren (eg, through an oral health curriculum in schools) for the maintenance of good oral health throughout life can provide them with the knowledge to make judicious choices about how they live their lives and preserve their health.…”
Section: Introductionmentioning
confidence: 99%
“…Poor oral health can harm children’s quality of life, academic performance and future achievements 8. Many children and parents in developing nations have limited awareness of the causes and prevention of the most frequent oral diseases 9. Oral health knowledge among Indian children is low when compared with their western counterparts 10.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, guardian-reported child oral health was found to be the most informative element in one recent machine learning based ECC screening application (21). Recent reports examining parental perceptions of young children's oral health in diverse settings (22)(23)(24)(25)(26) demonstrate the value and practical utility of understanding the agreement between self-reports and actual clinical status or treatment needs, as well as factors influencing them. Studies among community samples (i.e., not actively dental care-seeking populations), preschool-age children (i.e., those whose oral health-related behaviors and care is entirely determined by their family environment), and diverse (i.e., multi-ethnic) populations are warranted.…”
Section: Introductionmentioning
confidence: 99%